Splenectomy enhances the therapeutic effect of adipose tissue‐derived mesenchymal stem cell infusion on cirrhosis rats. (1st October 2015) - Tang, Wei‐Ping; Akahoshi, Tomohiko; Piao, Jing‐Shu; Narahara, Sayoko; Murata, Masaharu; Kawano, Takahito; Hamano, Nobuhito; Ikeda, Tetsuo; Hashizume, Makoto
Abstract: Background & Aims: Clinical studies suggest that splenectomy improves liver function in cirrhotic patients, but the influence of splenectomy on stem cell transplantation is poorly understood. This study investigated the effect of splenectomy on stem cell infusion and elucidated its mechanism. Methods: Rat adipose tissue‐derived mesenchymal stem cells were infused into cirrhosis rats with or without splenectomy, followed by the assessment of the in vivo distribution of stem cells and pathological changes. Stromal cell‐derived factor‐1 and hepatocyte growth factor expression were also investigated in splenectomized cirrhosis patients and rats. Results: Splenectomy, prior to cell infusion, improved liver function and suppressed fibrosis progression more efficiently than cell infusion alone in the experimental cirrhosis model. Stromal cell‐derived factor‐1 and hepatocyte growth factor levels after splenectomy were increased in patients and rats. These upregulated cytokines significantly facilitated stem cell motility, migration and proliferation in vitro . C‐X‐C chemokine receptor type 4 neutralization weakened the promotion of cell migration by these cytokines. The infused cells integrated into liver fibrosis septa and participated in regeneration more efficiently in splenectomized rats. Direct coculture with stem cells led to inhibition of hepatic stellate cell proliferation. In addition, hepatocyte growth factor induced hepatic stellate cell apoptosis via the c‐jun N‐terminal kinase‐p53 pathway. Conclusions: Splenectomy prior to cell infusion enhanced the therapeutic effect of stem cells on cirrhosis, which involved upregulation of stromal cell‐derived factor‐1 and hepatocyte growth factor after splenectomy.